Habitação de interesse social ou segregação induzida? um estudo sobre o Conjunto Pérolas do Rio Branco em Boa Vista-RR - Soares, Vera Mônica Araújo (Universidade Federal de Roraima, 2018)
From the end of the nineteenth century, Brazil began a process of urbanization more accelerated than its initial process at the beginning of its colonization. Cities have been emerging and growing, and this dissertation aims to carry out a study on the issue of Social Interest Housing in the municipality of Boa Vista in its urban area: a case study of the Pérolas do Rio Branco. In this way, this research sought to generate knowledge for the reflection of the practices related to the housing problem in Boa Vista. The right to housing, as various national and international instruments emphasize, is not restricted to the presence of a shelter or a roof, but encompasses a broader conception, so that the whole society and each of its members must have access to a housing provided with basic infrastructure and other facilities, that is, access to adequate housing. Without these rights individuals would fail to fully develop their potentialities. This work will focus specifically on one of these rights, which is the right to housing. As a methodology for this investigation, a documentary survey was carried out with the agencies related to housing issues such as the Municipal Government of Boa Vista, Municipal Social Management Secretariat (SEMGES), SETRABES, Caixa Econômica Federal and CODESAIMA (Development Company of the State of Roraima) and private companies linked to the construction of houses such as Renovo, in order to obtain documents for an approach on housing and the production of the urban space in Boa Vista and also an on-site survey with the application of questionnaires and photographic survey to know the profile of the residents of the neighborhood, from a bibliographical review, indicators were constructed to analyze relevant aspects regarding Social Interest Housing over several decades in different governments in the country. The results obtained showed that despite numerous housing programs and projects over the last decades, these do not fully meet the housing problem of Boa Vista.